Is water consumption embedded in crop prices? A global data-driven analysis. (21st September 2020) - Falsetti, Benedetta; Vallino, Elena; Ridolfi, Luca; Laio, Francesco
Abstract: Agricultural production exploits about 70% of all water withdrawals around the globe, but to date, it is not clear if and how this water consumption is taken into consideration in the price of the agricultural primary goods. To shed light on this point, we analyze the farm gate prices of twelve representative crops in the period 1991-2016, considering data from 162 countries in total. The crop price dependence on the water footprint is investigated, also accounting for the country's water scarcity as a possible additional determinant of the price, and of the land footprint as a possible confounding factor. We find that prices of staple crops (e.g. wheat, maize, soybeans, and potatoes) typically embed the amount of water used for their production. Differently, food products that do not contribute in an essential way to the human diet and whose production is more export-oriented (e.g. coffee, cocoa beans, tea, vanilla) exhibit weaker or negligible water-price links. These variations may be ascribable to specific market dynamics related to the two product groups. Staple crops are often produced in markets where many producers have more space for price setting and may have an incentive to include also the value of water in the final crop price. In contrast, cash crops are cultivated in situations where few producers are 'price takers' with respect to the international market. This mechanism may decrease the influence of the water used on crop farm gate price composition. The understanding of different water impacts on crop prices may be useful for increasing efficiency in water allocation and governance decisions, with the aim of improved environmental sustainability in this domain.